COMPARATIVE ANALYSIS OF FINITE ELEMENT MODELS OF PILE FOUNDATION IN COOPERATION WITH THE BASE - Tiutkin, O. L.; Hulak, A. V. (Science and Transport Progress, 2010)
In this article the comparative analysis of the tensed and deformed state of the finite-element models of «pile foundation – soil massif» system is presented.